2010
DOI: 10.1039/c0cc00486c
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative dimerization of N-protected and free indole derivatives toward 3,3′-biindoles via Pd-catalyzed direct C–H transformations

Abstract: An oxidative homo dimerization of N-protected and free indole derivatives toward bioactive 3,3-linked biindolyl scaffolds via Pd-catalyzed direct C-H transformations was first successfully demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…1 However, most of the methods for arene homocoupling use polyfluorobenzene, five-membered- ring heterocycles, or phenol starting materials. 2 Cross-coupling of heterocycles and acidic arenes with each other or simple benzene derivatives is also possible. 3 In rare cases when simple arenes such as toluene are coupled, isomer mixtures of products are usually obtained.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, most of the methods for arene homocoupling use polyfluorobenzene, five-membered- ring heterocycles, or phenol starting materials. 2 Cross-coupling of heterocycles and acidic arenes with each other or simple benzene derivatives is also possible. 3 In rare cases when simple arenes such as toluene are coupled, isomer mixtures of products are usually obtained.…”
mentioning
confidence: 99%
“…Furthermore, very few reports describe dehydrogenative arene couplings that do not require second-row transition metals as catalysts or additives. 2f,3d,e,9g …”
mentioning
confidence: 99%
“…This indicated that phenyl tosylate was much more reactive than iodobenzene, bromobenzene and phenylboronic acid under our reaction conditions. Furthermore, when Cu(II) was replaced by Cu(I) based on the standard conditions, we found the desired yields decreased sharply, which indicated that the transformation was more likely via a Cu(I)-catalyzed pathway (Table 1, entries [11][12][13][14][15][16]. Then (cinnamoyloxy)copper(I) was also prepared to investigate the reaction with phenyl tosylate, and only 10% yield of (E)-1,2-diphenylethene was obtained (Scheme 2, equation (4)).…”
Section: Resultsmentioning
confidence: 98%
“…Biindole ( 16 ) has previously been prepared by a palladium catalyzed oxidative dimerization of 5-bromoindole, 12 reductive cyclization of 17 , 13 and a two-step procedure employing a nucleophilic addition of 5-bromoindole ( 18 ) to 5-bromoisatine ( 19 ) followed by borane reduction of the intermediate (Scheme 5). 14 The 1 H NMR and 13 C NMR data recorded for 16 were in complete accordance with the reported values.…”
Section: Resultsmentioning
confidence: 99%
“…Compound 23 has previously been prepared via a palladium catalyzed oxidative dimerization of 6-bromoindole. 16 …”
Section: Resultsmentioning
confidence: 99%